Pedia Tricks - Out-of-the-Box Thinking in Paediatric Dentistry - Varsha Sharma; Brahmananda Dutta; Anandamoy Bagchi; Yashshwini Shroff (Indian Journal of Dental Research)
Noncooperative behaviour faced by a paediatric dentist is the most common attribution towards behavioural manifestations of anxiety in children, and it had been observed that these relationships are long—deterministic and form part of the aforementioned belief system of the child. Forehead and Long in their study found that most uncooperative behaviour of the child is due to their strong will and these children are generally confident, persistent and independent. A fruitful method to deal with strong willed children is to violate the causal relationship by some magic tricks from preventive via curative to his/her follow ups visits. Tricks can be applied at three levels of their visit. Level 1 is preoperative tricks, which includes the preventive measures that teach and educate children for good oral health. Level 2 is operative tricks, which involves child preparedness for successful dental procedures. Level 3 is postoperative tricks, which involve positive reinforcement for regular follow ups. The purpose of this review is to make paediatric dentists think like magicians by using the science behind the magic and applying it in their practice for creating a positive attitude of a child toward dentistry and better procedural experience.